(untitled) (Eurasian Journal of Engineering and Technology, 2022)
This article covers the development of building materials and more important mechanical and comprehensive information from various building materials physical properties, the influence of various factors on these properties, the causes of defects, methods of their prevention and treatment; material testing. An attempt was also made to submit to the reader about the general use and application of various materials.